Secondary Prevention of Cervical Cancer: ASCO Resource-Stratified Clinical Practice Guideline. Issue 5 (May 2017) - Jeronimo, Jose; Castle, Philip E.; Temin, Sarah; Denny, Lynette; Gupta, Vandana; Kim, Jane J.; Luciani, Silvana; Murokora, Daniel; Ngoma, Twalib; Qiao, Youlin; Quinn, Michael; Sankaranarayanan, Rengaswamy; et al.
Abstract : (Abstracted from J Global Oncol 2017; DOI:10.1200/JGO.2016.006577) The aim of the guideline was to provide global resource-stratified, evidence-based recommendations on the secondary prevention of cervical cancer, while accounting for wide variations in resource levels and health systems. These are the first cervical cancer screening guidelines that offer recommendations tailored to resource availability in the settings where women live.